Efektivitas Ketentuan tentang Hak Restitusi Sebagai Bentuk Perlindungan Hukum Bagi Anak Korban Tindak Pidana - Harly Stanly Muaja; Roy Ronny Lembong (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
The purpose of the research is to identify legal regulations, filing procedures, and obstacles to filing compensation for victims of criminal acts. This research was also carried out with a normative legal approach using secondary data processing data from primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of normative research with a legal approach, it can be concluded that 1) The rules on the rights of child victims of criminal acts have been regulated in detail in various Indonesian regulations and laws. 2) The effectiveness of implementing the law for child victims of criminal acts by making government regulations as additional penalties in criminal case decisions, in addition to corporal punishment and fines as the main penalties, will be difficult to achieve, so that legal certainty for the Implementation of Restitution for Child Victims of Criminal Acts cannot be implemented.